Metaphysics of Yoga in the Gheranda Samhita Scripture - Widya Sena, I Gusti Made; Putu Adnyana, Ida Bagus; Arsa Wiguna, I Made (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
The background of this research is that, apart from interpreting the verses related to God and yoga practice contextually, it also aims to analyse the metaphysics of yoga in the Gheranda Samhita book so that the knowledge gained by academics and yoga practitioners is more comprehensive. Metaphysics is full of discussions relating to God, the soul, eschatology, and illusory things. Moreover, if you study it using the postulates in a script as a limitation to sharpen the perspective that will be born, one script that can be used as a reference for understanding the dimensions of metaphysics is the Gheranda Samhita. Through descriptive qualitative methods, using hermeneutic theory, this research found the following findings: First, apart from Shiva as an aspect of God's representation as described in the Gheranda Samhita script, there are still other aspects of God that can represent His greatness. Second, it is through soul awareness that humans can achieve perfect awareness in living life. Third, there are no shackles like Maya, the term which is identified with the words illusion or bondage. Fourth, karma: actions in life. Fifth, Ahamkara, is another term for ego, and Sixth, Brahman and its Prakrti activities.